Comparative Study of Steel Mill Dust Leaching with Phosphoric Acid and Sodium Hydroxide - Fernando Sánchez; Ernesto de la Torre; Alicia Guevara; Katherine Moreno; Carlos F. Aragón-Tobar (Metals)
Steel mill dust (SMD), produced by electric arc furnaces, is a highly polluting industrial waste due to its high content of metals (Zn, Fe, and Pb) and fine particle size (ca. 5.4 µm). This residue can be valorized to recover Zn using pyro and hydrometallurgical methods, with hydrometallurgy offering greater selectivity and lower energy costs. However, composition of SMD presents a challenge in identifying an optimal leaching agent. This study investigates the preferential extraction of Zn using two leaching agents, namely 150 g L−1 (1.5 M) phosphoric acid (H3PO4) and 240 g L−1 (6 M) sodium hydroxide (NaOH), in a two-stage leaching process (80 °C). Metallic Zn from the alkaline pregnant solution was recovered by electrodeposition (750 A/m2, graphite anode, stainless-steel cathode) and smelting (450 °C). The samples of SMD contained 26.3% Zn, 20.1% Fe, and 0.9% Pb, in compounds such as magnetite (Fe3O4), zincite (ZnO), and franklinite (ZnFe2O4). Each leaching agent successfully attained a 99% Zn recovery, demonstrating the proposed procedure’s high efficacy. However, H3PO4 leached also Fe and corroded the cathode during electrodeposition, thereby restricting the final recovery of metallic Zn. NaOH demonstrated greater selectivity for Zn over Fe and Pb, producing high-purity Zn deposits on the cathode by electrodeposition and 99% metallic zinc by smelting.